Thermal and chemical modifications of diatomite from Peru and its application in the adsorption of cadmium - Manuel Chavez-Ruiz; Gloria A. Cosco-Salguero; Betsabé Ruffner-Camargo (Boletín de la Sociedad Española de Cerámica y Vidrio)
A physicochemical characterization was performed on a pennate-type diatomite of lacustrine origin from the southern region of Peru. Diatomite treatments were conducted with the goal of applying this material in adsorption of cadmium, various physical and chemical modifications were carried out, including thermal treatment and modifications with hydrochloric acid, sulfuric acid, and sodium hydroxide. A composite with cellulose and sulfuric acid was also prepared, and finally, a chelating agent EDTA (Ethylenediaminetetraacetic acid) was added. The thermal modifications showed weakly bound hydroxyl groups on the surface, originating from adsorbed water, as well as strongly bound hydroxyl groups from silanol group, as observed in FTIR (Fourier Transform Infrared Spectroscopy) studies. Higher adsorption capacity of cadmium values were obtained in samples modified with 0.5 M NaOH post thermal modification at 700 °C. SEM analysis showed a uniform distribution of cadmium on the diatomite surface. However, modifications with cellulose and sulfuric acid, as well as EDTA, did not significantly increase cadmium adsorption. Resumen: Se realizó una caracterización fisicoquímica de una diatomita tipo pennada de origen lacustre de la región sur del Perú. Se realizaron tratamientos de diatomita con el objetivo de aplicar este material en la adsorción de cadmio, se efectuaron diversas modificaciones físicas y químicas, incluyendo tratamiento térmico y modificaciones con ácido clorhídrico, ácido sulfúrico e hidróxido de sodio. También se preparó un compuesto con celulosa y ácido sulfúrico, y finalmente, se agregó un agente quelante ácido etilendiaminotetraacético (EDTA). Las modificaciones térmicas mostraron grupos hidroxilo débilmente unidos en la superficie, originados del agua adsorbida, así como grupos hidroxilo fuertemente unido del grupo silanol, como se observó en estudios FTIR. Se obtuvieron mayores valores de capacidad de adsorción de cadmio en muestras modificadas con NaOH 0,5 M posmodificación térmica a 700 °C. El análisis SEM mostró una distribución uniforme de cadmio en la superficie de la diatomita. Sin embargo, las modificaciones con celulosa y ácido sulfúrico, así como EDTA, no aumentaron significativamente la adsorción de cadmio.